Republic of Madagascar : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria, Modification of Performance Criteria, and Augmentation of Access-Staff Report; Staff Supplement and Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Republic of Madagascar. (IMF Staff Country Reports; Country Report, 2008)
This paper discusses key findings of the Fourth Review Under the Poverty Reduction and Growth Facility (PRGF) for Madagascar. Program performance has been generally good. The authorities have continued to implement sound fiscal and monetary policies that have resulted in good macroeconomic outcomes. They met all of the quantitative performance criteria (PCs) for end-January 2008, but missed two structural PCs. The international reserves cover is expected to deteriorate markedly, prompting the authorities to ask for an augmentation of 15 percent of quota, a request that IMF staff supports.